Investigation Geological structural morphology of Quaternary sediment on coastal Bac Lieu - Giảng, Nguyễn Văn; Thanh, Lê Ngọc (Vietnam Journal of Earth Sciences, 2018)
Georadar is a high-resolution near-surface geophysical method which employ radio waves, typically in the 1 to 1000 MHz frequency range tomap structure and features buried in the ground (or in man-made structures). Georadar method with Pulse EKKO 1 OOA instrument offers the highest resolution and rapidly provides continuous graphicformat which permits rapid semi-quantitative interpretation for in-field analysis. VLF method with Wadi instrument records the ratio of the strengths of the vertical and horizontal fields at the ground surface. Then this method can be used to reveal steeply dipping structures with large cross-sections and low resistivities as fructure/ conductivity zones.This paper is presented the result of using Georadar, VLF and electrical profiling methods for geological structural morphology of quaternarysediment investigation on coastal Baclieu. The structural cross-section of morphology of quaternary sediment is established by nine layers of georadar data for shallow structure and several interfaces of conductivity for deeper structure.